2004
DOI: 10.1128/mcb.24.10.4571-4580.2004
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Subtelomeric DNA

Abstract: There is a discrepancy in telomere length as measured by signal intensity of telomere restriction fragments on gels and fluorescence in situ hybridization analysis. This difference has been ascribed to the X-region, a segment of subtelomeric DNA that is resistant to being cut by restriction enzymes. To explore the nature of this region, we analyzed the digestibility of an artificial seeded telomere in HeLa cells as well as the Xp/Yp autosomal telomere in human BJ fibroblasts. We found that there is a substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 35 publications
(42 reference statements)
1
43
1
1
Order By: Relevance
“…In particular, both telomeres and subtelomeres are enriched in histone marks characteristic of constitutive heterochromatin, including trimethylated H4K20 and H3K9, as well as are bound by the heterochromatin protein 1 isoforms (HP1a, HP1b and HP1g) (Garcı´a-Cao et al, 2004;Gonzalo et al, , 2006Benetti et al, 2007b;reviewed in Blasco, 2007). In addition, subtelomeric DNA repeats are heavily methylated both in humans and mice (Steinert et al, 2004;Fraga et al, 2005;Gonzalo et al, 2006). These epigenetic marks at telomeres and subtelomeres are characteristic of a compacted chromatin state, and have been demonstrated to act as negative regulators of telomere length.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, both telomeres and subtelomeres are enriched in histone marks characteristic of constitutive heterochromatin, including trimethylated H4K20 and H3K9, as well as are bound by the heterochromatin protein 1 isoforms (HP1a, HP1b and HP1g) (Garcı´a-Cao et al, 2004;Gonzalo et al, , 2006Benetti et al, 2007b;reviewed in Blasco, 2007). In addition, subtelomeric DNA repeats are heavily methylated both in humans and mice (Steinert et al, 2004;Fraga et al, 2005;Gonzalo et al, 2006). These epigenetic marks at telomeres and subtelomeres are characteristic of a compacted chromatin state, and have been demonstrated to act as negative regulators of telomere length.…”
Section: Introductionmentioning
confidence: 99%
“…11 Similar to pericentromeric regions, subtelomeres have a high density of DNA repeats and CpG islands, which are susceptible to DNA methylation by DNA methyltransferases (DNMTs). 12,13 Telomeres, however, do not contain CpG sequences.…”
mentioning
confidence: 99%
“…Currently relatively little is known about epigenetic modification of telomeric or subtelomeric DNA in human cells although one study of the human Xp/Yp telomere indicated that a region immediately adjacent to the telomere is modified in some way but not just by CpG methylation (Steinert et al, 2004). In another study it was shown that subtelomeric regions were hypomethylated in human ICF cells that have reduced DNMT3B.…”
Section: Chromatin and Altmentioning
confidence: 96%